Методи і механізми маніпулятивного впливу в сучасному суспільстві - Ладченко, М. В. (ХНУРЕ, 2024)
The development of modern society, which is characterized as an information society, is accompanied by rapid rates of informatization of all spheres of human activity. One of the negative factors of informatization is that information acts as a certain mechanism for manipulating society. The work defines "manipulation" and examines modern methods and mechanisms of manipulative influence on human consciousness
Keywords: маніпулятивний вплив; information society